Couple Relationships in the 21st Century Research, Policy, Practice - Gabb, Jacqui (Palgrave Macmillan Studies in Family and Intimate Life, 2018)
This book presents an incisive and engaging account of love, intimacy and personal life in contemporary Western society. The authors draw on rich qualitative and large-scale survey data to explore how couples communicate with each other, negotiate the pressures and pleasures of parenthood, and the vagaries of sexual desire and intimacy across life course. Focusing on 'the everyday', Couple Relationships in the 21st Century unpicks the ordinary and often mundane relationship work that goes into sustaining a relationship over time, breaking down the dichotomy between enduring relationships of quality and good enough or endured relationships. It contests the separation of couples into distinct relationship types - defined through age, parenthood or sexuality. Looking through the lens of relationship practices it is clear that there is no 'normal couple': couples are what couples do. With a foreword by Dr Reenee Singh, Director, London Intercultural Couples Centre and Co-Director, Tavistock Family Therapy and Systemic Research Centre, this new extended edition provides an invaluable critical insight on contemporary experiences of coupledom and will be essential reading for scholars and students, clinicians working in couple and family therapy, and those involved in relationship support services.